HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG ANEMIA DENGAN RISIKO KEJADIAN BBLR - Siti Fatimah; Nopita Dewi Kania (Universitas Galuh, 2019)
Infant Mortality Rate (IMR) in Indonesia is still relatively high. LBW is one of the causes of neonatal death, in addition to Birth Trauma, Asphyxia, Infection, Tetanus Neonatorum (TN), Congenital Abnormalities and Others. Increasing the knowledge of pregnant women is a strategic effort in achieving the decrease of infant mortality rate. This study aims to determine the relationship between the knowledge level of pregnant mothers about anemia with the risk of BBLR occurrence in the working area of Baregbeg Puskesmas 2018. The research design used is analytical descriptive using cross sectional study design. The measuring tool used in this study is a questionnaire sheet to identify the level of knowledge of pregnant women about anemia and observation sheet to determine the height of the mother's uterine fundus to calculate the estimated weight of the fetus so that it can see the risk or not risk of LBW occurrence. The sampling technique used was accidental sampling with a total sample of 15 people. Chi-Square correlation test results obtained value of 0.596 with a value of ? value of 0.016. The value of ? value of 0.016 is smaller than ? (0.05). Mothers with a good level of knowledge of 7 people (46.6%) and mothers who did not risk the occurrence of BBLR as many as 10 people (66.6%). This shows that there is a significant correlation between maternal knowledge level about anemia with risk of LBW occurrence. Maternal knowledge about anemia is very important as one of prevention of anemia during pregnancy and risk of LBW incidence. Expected to increase mother's knowledge about anemia in pregnant mother and prevent the risk of occurrence of LBW as well as development of science and research methodology.Keywords : Knowledge Level, Pregnant Woman and Low Birth Weight, Anemia.